CONGENITAL HEART DEFECTS, EXAMINATION METHODS AND MANAGEMENT TACTICS IN THE NEONATAL PERIOD - Akramov Firdavs Feruzkhon ugli; Tishabaeva Nargiza Alimdjanovna (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article under discussion reveals congenital heart defects examination methods and management tactics in the neonatal period. The authors of the article consider that the right standard for congenital heart defects diagnosis is the echo-CG and the main challenge is the development of prenatal diagnosis. But even without echo-CG available, an attentive and competent physician can make a preliminary diagnosis and provide the right and timely help to a patient with congenital heart defects.